The Influence of Color and Label Information on Flavor Perception - Shankar, M; Levitan, C; Prescott, J; Spence, C (2009)
Previous research that has manipulated either the color of, or labeling information associated with, foods and beverages has shown that each of these factors can significantly influence perceptual and preferential responses to them. The present study examined how the simultaneous manipulation of these two cues (color and label) affects perception of, and hedonic responses to, flavor. Thirty participants rated 12 chocolate MandMs (identical aside from their color), described as coming from a "new line of chocolate products," for the intensity of their chocolate flavors ("chocolatey-ness") and their hedonic qualities ("likeability"). In the color-only condition, sighted participants received two green and two brown MandMs. In the label-only condition, blindfolded participants received two MandMs that were labeled as being from a "milk chocolate category" and two MandMs that were labeled as being from a "dark chocolate category." In the color-label condition, sighted participants received an MandM of each of the four possible color-label combinations. The participants rated brown MandMs as being significantly more chocolatey than green MandMs and "dark chocolate"-labeled MandMs as being significantly more chocolatey than "milk chocolate"-labeled ones. No such effects were observed for the likability data. There was no interaction between the color and label factors. These results illustrate that flavor perception involves the combining of chemosensory information with both visual (color) information and cognitive, expectancy-based (label) inputs. © 2009 Springer-Verlag.